A new DNA extraction protocol for screwworm fly Cochliomyia species (Diptera: Calliphoridae) - Echeverría-Fonseca, Gustavo; Mera-Ruiz, Patricia A.; Carrillo-Toro, Jenny; Rodriguez-Hidalgo, Richar (Frontiers in Environmental Science, 2015)
Modifications to the DNA isolation protocol from Cochliomyia spp., are suggested based on the Chelex® 100 reactive. To apply the sterile insect technique (SIT) program it is necessary to study the molecular variations of endemic populations with efficient, fast and low costs techniques. The test samples were collected in the Pichincha province of Ecuador. The isolation protocol had 3 steps: a) pretreatment (optional), b) mechanic and chemical lysis, c) two incubations; then the supernatant were separated by centrifugation. Furthermore, variations in concentrations of magnesium chloride present in the master mix were evaluated. Results showed a high efficiency in isolation with approximately 1.20 hours of manipulation (without pretreatment). Additionally, the quality of the amplicon that was visualized on 2% agarose (w/v) showed that the magnesium chloride concentration was influential in the PCR reaction mix.